Home gardens in the maintenance of biological diversity - O.M., Agbogidi; E. B., Adolor (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Home garden is an integrated system which comprises different things in its small area that produces a variety of foods and agricultural products including staple crops, vegetables, fruits, medicinal plants and so on. In this context, the role of home garden as repositories of biological diversity is acknowledged. Home gardens, whether found in rural or urban areas, are characterized by a structural complexity and multi-functionality which enables the provision of different benefits to ecosystems and people. High levels of inter- and intra-specific plant genetic diversity are preserved in home gardens. Home gardens are important social and cultural spaces where knowledge related to agricultural practice is transmitted and through which households may improve their income and livelihood. The biological and cultural significance of agro-biodiversity in home gardens are highlighted with the future constraints and opportunities in home garden research in the prospect of defining and promoting their role in conservation of agricultural biodiversity and cultural heritage.